The Iterative Development of Medicines Through the European Medicine Agency's Adaptive Pathway Approach - Nicotera, Giuseppe; Sferrazza, Gianluca; Serafino, Annalucia; Pierimarchi, Pasquale (Frontiers in Medicine, 2019)
The development of novel regulatory tools such as adaptive clinical trial design and utilization of real-world evidence are topics of high interest. Recently, the European Medicines Agency (EMA) introduced the Adaptive Pathways (AP) that represents an innovative tool in healthcare systems allowing the early dialogue with multiple stakeholders on promising and innovative medicinal products in areas with an high unmet medical need. The innovative aspect in the AP is the early involvement of several stakeholders such as pharmaceutical industry, the Academia, Health Technology Assessment (HTA) bodies and patient representatives bringing their real experience with the disease and their expectations about the treatment. AP is not a new licensing tool but an opportunity for a very early discussions, before starting the phase II studies, among all stakeholders, including regulators, companies, HTA bodies, and patient representatives on a new potential medicine in areas of high unmet medical need. The aim of this paper is to describe the evolution of the AP approach from the beginning of the pilot project to date, highlighting major advances and achievement at European level.